Respuesta :
Let's solve your equation step-by-step.13(x−2)=15(x+4)+2Step 1: Simplify both sides of the equation.13(x−2)=15(x+4)+2(13)(x)+(13)(−2)=(15)(x)+(15)(4)+2(Distribute)13x+−23=15x+45+213x+−23=(15x)+(45+2)(Combine Like Terms)13x+−23=15x+14513x+−23=15x+145Step 2: Subtract 1/5x from both sides.13x+−23−15x=15x+145−15x215x+−23=145Step 3: Add 2/3 to both sides.215x+−23+23=145+23215x=5215Step 4: Multiply both sides by 15/2.(152)*(215x)=(152)*(5215)x=26Answer:x=26
The first step is to simplify both sides of the equation to 1/3x+-2/3=1/5x+14/5-1/5x
subtract 1/5x from both sides
1/3×+-2/3-1/5×=1/5×+1/5×+14/5-1/5×
2/15×+-2/3=14/5
add 2/3 to both sides.
2/15×+-2/3+2/3=14/5+2/3
2/15=52/15
multiply both sides by 15/2
(15/2)*(2/15×)=(15/2)*(52/15)
x=26.
hope this helps!
subtract 1/5x from both sides
1/3×+-2/3-1/5×=1/5×+1/5×+14/5-1/5×
2/15×+-2/3=14/5
add 2/3 to both sides.
2/15×+-2/3+2/3=14/5+2/3
2/15=52/15
multiply both sides by 15/2
(15/2)*(2/15×)=(15/2)*(52/15)
x=26.
hope this helps!